2020
DOI: 10.3389/frobt.2020.00099
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Social Robot to Tablet and Teacher in a New Script Learning Context

Abstract: This research occurred in a special context where Kazakhstan's recent decision to switch from Cyrillic to the Latin-based alphabet has resulted in challenges connected to teaching literacy, addressing a rare combination of research hypotheses and technical objectives about language learning. Teachers are not necessarily trained to teach the new alphabet, and this could result in a challenge for children with learning difficulties. Prior research studies in Human-Robot Interaction (HRI) have proposed the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 69 publications
1
22
0
Order By: Relevance
“…Accordingly, the knowledge summarized here sustains the importance of adopting a systemic approach even in the evaluation of the impact of supposedly purely visual deficits, which indeed can affect also motor skills, cognition, social skills, and emotional processing. Addressing such a complexity is the fundamental requirement of current implementations of systemic approaches for visuallyrelated training in typical conditions or in response to visual disorders, including virtual reality (Adams et al, 2018;Choi et al, 2021), robotics (Mirkowski et al, 2019;Zhexenova et al, 2020), and touch screen technology (Aslam et al, 2016;Sheehan and Uttal, 2016;Dalecki et al, 2019).…”
Section: Final Remarksmentioning
confidence: 99%
“…Accordingly, the knowledge summarized here sustains the importance of adopting a systemic approach even in the evaluation of the impact of supposedly purely visual deficits, which indeed can affect also motor skills, cognition, social skills, and emotional processing. Addressing such a complexity is the fundamental requirement of current implementations of systemic approaches for visuallyrelated training in typical conditions or in response to visual disorders, including virtual reality (Adams et al, 2018;Choi et al, 2021), robotics (Mirkowski et al, 2019;Zhexenova et al, 2020), and touch screen technology (Aslam et al, 2016;Sheehan and Uttal, 2016;Dalecki et al, 2019).…”
Section: Final Remarksmentioning
confidence: 99%
“… Park et al, 2011 ; Serholt et al, 2014 ; Kennedy et al, 2016a ; Kory Westlund et al, 2017 ). Another study compared a robot tutee to a human teacher, as well as to a tablet-only condition ( Zhexenova et al, 2020 ). Chandra et al (2015) compared a robot facilitating a learning-by-teaching scenario between two children to a human facilitator.…”
Section: Introductionmentioning
confidence: 99%
“…Current evidence on the effectiveness of robot-assisted language learning (RALL), however, is mixed (see for reviews Kanero et al, 2018 ; van den Berghe et al, 2019 ), and there is inconclusive evidence on the possible benefits of robots over other forms of technology ( Han et al, 2008 ; Hyun et al, 2008 ; Leyzberg et al, 2012 ; Gordon et al, 2015 ; Kory Westlund et al, 2015 ; Zhexenova et al, 2020 ). Specific for word learning, positive effects of robots on learning were found in several single-session studies ( Tanaka and Matsuzoe, 2012 ; de Wit et al, 2018 ), while only moderate learning gains were found in multiple-session studies ( Kanda et al, 2004 ; Gordon et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%